Innovative cooling solutions of HPDC technology - Bratu, Zoltán Ferenc; Erdélyi, János Péter; Molnár, Dániel (Multidiszciplinaris Tudomanyok, 2024)
In High Pressure Die Casting (HPDC), the so-called sliders are moving components of the mould, that can form cavities, holes, and undercuts. Sliders differ greatly from fixed- and moving mould halves regarding cooling and thermal balance. Typically, mould halves can range from a few hundred kilograms to several tonnes in size, whereas sliders have a significantly lower mass, and therefore their thermal balance changes much more drastically during casting cycles. Sliders can also be used to improve local heat dissipation in different areas. They are equipped with cooling holes through which the hole-forming cores, which penetrate deep into the mould cavity, can be tempered so that a significant amount of heat can be removed from the solidifying metal during the mould-filling process. As the industry produces increasingly complex castings, the cooling systems for the various moulds, inserts and cavities have evolved accordingly as the complexity of the castings has increased. This has resulted in innovative solutions and developments in the cooling of moulds and mould inserts, such as the use of 3D-printed metal inserts with improved heat dissipation. This article compares the cooling differences between traditionally cooled and 3D-printed sliders. We investigate cooling efficiency and tool temperatures at different cooling intensities through simulation experiments. Furthermore, at the end of the solidification phase, we examine the mold temperatures and the heat extracted for different molds and cooling intensities.